Distinct gene expression profiles underlie morphological and etiological differences in pediatric cataracts - Shanbagh, Shaika; Matalia, Jyoti; Kannan, Ramaraj; Shetty, Rohit; Panmand, Pratibha; Muthu, Sumitha O; Chaurasia, Shyam S; Deshpande, Vrushali; Bhattacharya, Shomi S; Gopalakrishnan, Abilash V; Ghosh, Arkasubhra (Indian journal of ophthalmology, 2023)
Purpose: Pediatric cataract is a major cause of preventable childhood blindness worldwide. Although genetic mutations or infections have been described in patients, the mechanistic basis of human cataract development remains poorly understood. Therefore, gene expression of structural, developmental, profibrotic, and transcription factors in phenotypically and etiologically distinct forms of pediatric cataracts were evaluated. Methods: This cross-sectional study included 89 pediatric cataract subjects subtyped into 1) prenatal infectious (cytomegalovirus, rubella, and combined cytomegalovirus with rubella infection), 2) prenatal non-infectious, 3) posterior capsular anomalies, 4) postnatal, 5) traumatic, and 6) secondary, and compared to clear, non-cataractous material of eyes with the subluxated lenses. Expression of lens structure-related genes (Aqp-0, HspA4/Hsp70, CrygC), transcription factors (Tdrd7, FoxE3, Maf, Pitx 3) and profibrotic genes (Tgfβ, Bmp7, αSmA, vimentin) in surgically extracted cataract lens material were studied and correlated clinically. Results: In cataract material, the lens-related gene expression profiles were uniquely associated with phenotype/etiology of different cataracts. Postnatal cataracts showed a significantly altered FoxE3 expression. Low levels of Tdrd7 expression correlated with posterior subcapsular opacity, whereas CrygC correlated significantly with anterior capsular ruptures. The expression of Aqp0 and Maf was elevated in infectious cataracts, particularly in CMV infections, compared to other cataract subtypes. Tgfβ showed significantly low expression in various cataract subtypes, whereas vimentin had elevated gene expression in infectious and prenatal cataracts. Conclusion: A significant association between lens gene expression patterns in phenotypically and etiologically distinct subtypes of pediatric cataracts suggests regulatory mechanisms in cataractogenesis. The data reveal that cataract formation and presentation is a consequence of altered expression of a complex network of genes.